Performance optimisation of Tesla valve-type channel for cooling lithium-ion batteries. (25th July 2022) - Lu, Yanbing; Wang, Jianfeng; Liu, Fen; Liu, Yiqun; Wang, Fuqiang; Yang, Na; Lu, Dongchen; Jia, Yongkai
Highlights: A cold plate cooling system with Tesla valve-type channels is proposed to improve the cooling effect on batteries. Tesla valve-type channel cold plate enhances heat exchange and improves temperature uniformity owing to the fluid disturbance caused by the bifurcated structure, especially under strong heat flux. Reverse Tesla valve-type channel cold plate with an angle of 120°, Tesla valve distance of 23.1 mm, channel distance of 28 mm, and inlet velocity of 0.83 m/s is recommended through multi-objective optimisation. The optimal cooling system controls the battery maximum temperature below 30.5 °C while maintaining a low channel pressure drop. Abstract: An efficient and energy-saving battery thermal management system is important for electric vehicle power batteries. Cold plate cooling systems with channels are widely used for lithium-ion batteries, and the optimisation of cold plate structure, channel shape, and number is the key to research. Inspired by the Tesla valve-type microchannel heat sink used in microelectronics, we propose a cold plate with Tesla valve-type channels for rectangular lithium-ion batteries. Compared with the Z-type channel, the Tesla valve-type channel enhances heat exchange and improves temperature uniformity owing to the fluid disturbance caused by its bifurcated structure, especially under strong heat flux. Moreover, based on an accurate battery thermal model at a discharge of 3C established through thermal characteristic experiments, a numerical simulation is conducted to analyse the influence of some factors, including the angle between adjacent Tesla valves, distance between adjacent Tesla valves, distance between adjacent channels, and coolant inlet velocity. Finally, the agent models of evaluation indicators with fit goodness greater than 97% are obtained through a central composite design. The multi-objective optimisation results show that the reverse Tesla valve-type channel cold plate with an angle of 120°, Tesla valve distance of 23.1 mm, channel distance of 28 mm, and inlet velocity of 0.83 m/s have a good balance between heat exchange performance and energy consumption, which controls the battery maximum temperature below 30.5 °C while maintaining a low channel pressure drop.